2011
DOI: 10.5398/medpet.2011.34.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Partial Coding Region Fibroin Gene on Wild Silkmoth Cricula trifenestrata Helfer (Lepidoptera: Saturniidae)

Abstract: The study was conducted to characterize coding region of wild silkmoth C. trifenestrata partial fi broin gene, and detect these gene potential as molecular marker. A total of six larvae C. trifenestrata were collected from Bogor, Purwakarta and Bantul Regency. Genomic DNA was extracted from silk gland individual larvae, then amplifi ed by PCR method and sequenced. DNA sequenced result was 986 nucleotide partial fi broin gene of C. trifenestrata, which are comprising complete coding region of fi rst exon (42 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…h‐fibroin is a large and highly repetitive gene whose product serves as a major component of silk fiber. Its nonrepetitive N‐terminal or C‐terminal sequence has been identified in several lepidopteran families such as Saturniidae, Bombycidae, Pyralidae, Yponomeutidae, and Hepialidae (Sezutsu & Yukuhiro, ; Fedič et al ., ; Yonemura & Sehnal, ; Sezutsu et al ., , b; Collin et al ., ; Sezutsu et al ., ; Suriana et al ., ). We found that the products of contig 27 (accession number LC001862) and contig 61 (LC001861) were homologous to the C‐termini and N‐termini of Bombyx H‐fibroin and other Saturniidae fibroins (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…h‐fibroin is a large and highly repetitive gene whose product serves as a major component of silk fiber. Its nonrepetitive N‐terminal or C‐terminal sequence has been identified in several lepidopteran families such as Saturniidae, Bombycidae, Pyralidae, Yponomeutidae, and Hepialidae (Sezutsu & Yukuhiro, ; Fedič et al ., ; Yonemura & Sehnal, ; Sezutsu et al ., , b; Collin et al ., ; Sezutsu et al ., ; Suriana et al ., ). We found that the products of contig 27 (accession number LC001862) and contig 61 (LC001861) were homologous to the C‐termini and N‐termini of Bombyx H‐fibroin and other Saturniidae fibroins (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Gene mapping of silkworm started in late 19's but the very first genetic map of silkworm was constructed by [14]. Gene mapping has led to the identification of 1018 genetic markers with an approximate interval of 500 kb, and it was carried out in twenty-seven autosomes and one Z chromosome [8]. By using backcross population, linkage map was constructed with 85 STS markers, 80 SSRM markers and 16 single nucleotide polymorphisms.…”
Section: Genetic Study Of Silkwormmentioning
confidence: 99%
“…Easy handling of silkworm makes it the second most successful organism in laboratories apart from drosophila. Since Lepidoptera contains some agricultural pests, so the genetic study of silkworm is helpful in their control [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The protein extraction was previously conducted by , adding 2 g/L (0.05 N) NaOH, 2 cc/L teepol, and 2 g/L neutral soap to boiling A. atlas cocoons at 80°C for 2 hours will produce a better character of the silk fiber in terms of fiber length and weight. The strong base NaOH 0.1 N is a solvent for degumming which produces the best fibroin of C. trifenestrata (Suriana 2011). Furthermore, the extraction with a combination of temperature, time, and solvent (NaOH) at a certain concentration is important to optimize sericin yields.…”
Section: Introductionmentioning
confidence: 99%